Investigating the impact of remittance outflows and oil price on economic growth in Gulf Cooperation Council countries - Mouyad Alsamara (17823668) (2023)
Most existing studies have focused on examining the impact of labor remittance outflows on economic growth in the receiving countries, with limited attention given to the sending countries. This study utilizes the nonlinear augmented mean group method to explore the possible asymmetric impact of remittance outflows on economic growth in Gulf Cooperation Council (GCC) countries for the period of 2000–2019. The results indicate that non-oil real GDP exhibits an adverse and magnified response to an increase in remittance outflows, relative to a decrease. Furthermore, this negative impact is amplified when accounting for oil price changes. These findings have significant implications for labor markets and nationalization policies in the GCC countries. Other Information Published in: Resources Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.resourpol.2023.103557